Animal models of PTSD: Comparison of the neuroendocrine and behavioral sequelae of immobilization and a modified single prolonged stress procedure that includes immobilization. (April 2023) - Sanchís-Ollé, María; Belda, Xavier; Gagliano, Humberto; Visa, Joan; Nadal, Roser; Armario, Antonio
Abstract: A single exposure to some stressors results in long-lasting consequences reminiscent of those found in post-traumatic stress disorder (PTSD), but results are very often controversial. Although there is no consensus regarding the best animal models of PTSD, the single prolonged stress (SPS) model, consisting of sequential exposure within the same day to various stressors (typically restraint, forced swim, and ether), has gained acceptance. However, results, particularly those related to the hypothalamic-pituitary-adrenal (HPA) axis, are inconsistent and there is no evidence that SPS is clearly distinct from models using a single severe stressor. In the present study, we compared in male rats the behavioral and neuroendocrine (HPA) consequences of exposure to immobilization on boards (IMO) with a SPS-like model (SPSi) in which IMO and isoflurane were substituted for restraint and ether, respectively. Both procedures caused a similar impact on food intake and body weight as well as on sensitization of the HPA response to a novel environment (hole-board) on the following day. Reduction of activity/exploration in the hole-board was also similar with both stressors, although the impact of sudden noise was higher in SPSi than IMO. Neither IMO nor SPSi significantly affected contextual fear conditioning acquisition, although a similar trend for impaired fear extinction was observed compared to controls. Exposure to additional stressors in the SPSi did not interfere with homotypic adaptation of the HPA axis to IMO. Thus, only modest neuroendocrine and behavioral differences were observed between IMO and SPSi and more studies comparing putative PTSD models are needed.